Current Problems of the Forensic Analysis of Handwriting and Signatures Made with Modern Technical Means - N. A. Rybalkin (Теория и практика судебной экспертизы, 2022)
The author considers one of the topical issues of forensic handwriting examination and forensic technical examination of documents – analysis of handwriting objects made using modern technical means: plotter, 3D printer, robotic hand.The author reviews the main publications on this topic, analyzes some methods for identifying such handwriting objects, systemizes the features helping to detect them. He also pays special attention to complex situations that occur in expert practice.The given recommendations on the work with handwriting objects made with modern technical means, their comprehensive analysis by handwriting experts and expert technicians will contribute to improving the quality of training of experts in these specialties.